Highly thermally conductive UHMWPE/graphite composites with segregated structures. Issue 70 (11th July 2016) - Feng, C. P.; Chen, L.; Wei, F.; Ni, H. Y.; Chen, J.; Yang, W.
Abstract : Polymer composites with segregated structures based on ultrahigh molecular weight polyethylene (UHMWPE) and graphite flakes were fabricated by a novel binder-mixing method and high thermal conductivity of the composites was achieved. Abstract : Polymer composites with segregated structures based on ultrahigh molecular weight polyethylene (UHMWPE) and graphite flakes were fabricated by a novel binder-mixing method and the traditional solvent-mixing method. Compared with the solvent-mixing method, the thermal conductivity of composites fabricated by the binder-mixing method improved on average by 26.27 percent at the volume fraction of graphite flakes from 2.22–18.83 vol%. Optical and SEM images showed that the binder-mixing method results in the formation of a more continuous and more homogeneous conductive network and wider thermally conductive paths, leading to the greatly improved thermal conductivity.